Response to bronchodilators in very preterm infants with evolving bronchopulmonary dysplasia - Morrow DK; Schilling D; McEvoy CT (Dove Medical Press, 2015)
Daniel K Morrow, Diane Schilling, Cindy T McEvoy Department of Pediatrics, Oregon Health and Science University, Portland, OR, USA Background: There are few effective and safe medications to treat very low birth weight (VLBW) infants with evolving bronchopulmonary dysplasia. Bronchodilators are often given to patients who have clinical signs of reactive airway disease, but there is not enough information regarding their effectiveness within this population. Objective: To quantify the pulmonary function response to bronchodilator therapy in a population of VLBW infants with evolving bronchopulmonary dysplasia. Materials and methods: This is a retrospective analysis of an ongoing large database of pulmonary function tests (PFTs) in premature infants. We reviewed the pre- and post-bronchodilator PFTs ordered by a physician due to concern for reactive airway disease. Inclusion criteria: Birth weight (BW) <1,500 g; >14 days of age; admission diagnosis of respiratory distress syndrome; requiring ongoing oxygen, continuous positive airway pressure, or ventilator support at the time of PFT. PFTs were done prior to albuterol therapy and repeated 30 minutes after the therapy was given. PFTs included the measurement of passive respiratory mechanics with the single breath occlusion technique, including passive respiratory system compliance, resistance, and tidal volume. Results: Forty VLBW infants (mean gestation of 27.4 weeks; mean BW of 848 g) were identified as having PFTs. Twenty-nine of these patients had a BW of ≤1,000 g. The patients were studied at a mean corrected gestational age of 34.9 weeks. Twenty-nine of 40 patients were extubated at the time of the PFT. Of these patients, 21 (52.5%) had a decrease in respiratory system resistance of ≥10%. From the other 19 patients, five (12.5%) had a decrease of 0% to <10% in respiratory system resistance, and 14(35%) showed no response to therapy. There was no significant difference in respiratory system compliance between the groups. Keywords: Albuterol, pulmonary function